Effects of Nutrition and Physical Activity in Prevention of Neurological and Cognitive Disorders- A Review Study - Shweta Patel; Diwakar Chauhan; Ranjana Patnaik (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: As neurodegenerative and psychiatric disorders are rising rapidly, unexpected demandfor cost-effective and practical treatment is also growing. The present study reveals the synergistic roleand mechanism of nutrition and physical activities in the transition of cognitive functions and mentalwellbeing.Objectives: To unravel the effect of nutrition and exercise in maintaining cognitive function and mentalhealth. In this study some of these points were reviewed such as what is the influence of nutritionand exercise over mental health. How well the combined effects can help to combat neurological andbehavioural disabilities. What mechanism is involved in promoting mental health.Methods: A non-systematic approach was used in the present review study. This study summarizes thesynergistic role and mechanism of nutrients and physical exercise in the transition of cognitive functionand mental balance.Results: The most important outcome is nutritional therapy in combination with regular physicalexercise is a reliable, effective and economical alternative that can intensify the effects of standard drugtherapy.